2009
DOI: 10.1002/art.24786
|View full text |Cite|
|
Sign up to set email alerts
|

Changes in surface markers of human mesenchymal stem cells during the chondrogenic differentiation and dedifferentiation processes in vitro

Abstract: Objective. To investigate surface markers showing specific changes during the chondrogenic differentiation and dedifferentiation of human mesenchymal stem cells (MSCs).Methods. Human MSCs from adult bone marrow were subjected to chondrogenic differentiation in 3-dimensional (3-D) alginate culture with or without transforming growth factor ␤3 (TGF␤3) for 2 weeks, followed by dedifferentiation in monolayer for 1 week. Surface antigens were selected from those previously reported to show changes in expression dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
64
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(83 citation statements)
references
References 29 publications
(31 reference statements)
18
64
0
1
Order By: Relevance
“…In agreement with Mareddy et al [2007] and Astori et al [2007], who observed low expression of CD271 in MSCs from adipose tissue, we observed that the expression of CD271 was below 16% in MSCs from all the tissues analysed. Grogan et al [2007] showed that CD44, CD49c and CD151 are expressed at high levels in chondrocytes with chondrogenic potential, and these molecules have also been described as useful flow cytometry markers for human bone marrow-derived MSCs [Lee et al, 2009]. In agreement with these results, we observed expression of these markers in MSCs from all tissues analysed.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In agreement with Mareddy et al [2007] and Astori et al [2007], who observed low expression of CD271 in MSCs from adipose tissue, we observed that the expression of CD271 was below 16% in MSCs from all the tissues analysed. Grogan et al [2007] showed that CD44, CD49c and CD151 are expressed at high levels in chondrocytes with chondrogenic potential, and these molecules have also been described as useful flow cytometry markers for human bone marrow-derived MSCs [Lee et al, 2009]. In agreement with these results, we observed expression of these markers in MSCs from all tissues analysed.…”
Section: Discussionsupporting
confidence: 88%
“…We found that approximately 30% of cells expressed CD54 (ICAM-1), in keeping with the percentage observed by Sakaguchi et al [2005] and Lee et al [2009] in human bone marrow-derived MSCs. CD54 expression was higher in subcutaneous fat-derived MSCs ( fig.…”
Section: Discussionsupporting
confidence: 88%
“…In chondrogenic medium, Thy1 mRNA level decreases deeply since day 7 of differentiation. These results are in accordance to the literature, where it was demonstrated that many MSCs markers among them Thy1 were decreased during 7 days of chondrogenic differentiation [56]. For nucleostemin and endoglin, mRNA level analysis did not show difference in cell in chondrogenic medium compared to MSCs.…”
Section: Discussionsupporting
confidence: 92%
“…4D). In contrast, CD105, a marker of human MSC that decreases in chondrogenesis culture (36), was higher in LV/HMGB2 control group. These findings suggest that sustained expression of HMGB2 in MSC blocks chondrogenic dif- ferentiation and maintains immature status of MSC even after chondrogenesis was induced.…”
Section: Hmgb2 Expression In Msc and Articularmentioning
confidence: 73%